Implementasi Pelayanan Publik Dalam Pengurusan Kartu Tanda Penduduk Elektronik Di Kecamatan Bukit Raya Dalam Peraturan Pemerintah Nomor 96 Tahun 2012 Tentang Pelaksanaan Undang-Undang Nomor 25 Tahun 2009 Pelayanan Publik - Fais Albar; Evi Deliana; Zulwisman Zulwisman (Peneliti.net, 2026)
This study aims to analyze the implementation of public services in the administration of the Electronic Identity Card (e-KTP) in Bukit Raya District, in accordance with Government Regulation Number 96 of 2012 concerning the Implementation of Law Number 25 of 2009 on Public Services. The background of this research is based on the phenomenon of numerous complaints submitted by residents of Bukit Raya District regarding the quality of public services, particularly in the e-KTP administration process. This raises questions concerning the established service standards and the factors that hinder their effectiveness. This research applies both qualitative and quantitative legal methods, using a juridical-sociological legal approach. Data sources consist of primary data obtained through interviews with the Head of the e-KTP Management Division at the Population and Civil Registration Office of Pekanbaru City, officers from the Integrated Administrative Services Section (PATEN) at the district level, and questionnaires distributed to the residents of Bukit Raya District. Secondary data were obtained through literature studies, including laws and regulations, academic literature, and relevant documents. The findings indicate that the implementation of public services in the administration of e-KTP in Bukit Raya District, as stipulated in Government Regulation Number 96 of 2012, has not been optimal. The research reveals that the competence of the human resources assigned to manage e-KTP remains inadequate, and their readiness to serve the public is still low. In addition, the quality of service provided by the operator staff does not yet meet public expectations. The socialization efforts that should be conducted by the Bukit Raya District authorities have also not been carried out effectively, resulting in limited information dissemination among the residents. In the implementation process of issuing the Electronic Identity Card (e-KTP), several obstacles are encountered, including limitations in equipment procurement and the lack of sufficient training or capacity-building for the operators involved. Furthermore, the level of discipline among government personnel tasked with assisting the public in the e-KTP registration process remains relatively low.